Spies of no country : secret lives at the birth of Israel - Friedman, Matti, 1977- (Algonquin Books of Chapel Hill, 2019)
"The four spies at the center of this story were part of a ragtag unit known as the Arab Section, conceived during World War II by British spies and Jewish militia leaders in Palestine. Intended to gather intelligence and carry out sabotage and assassinations, the unit consisted of Jews who were native to the Arab world and could thus easily assume Arab identities. In 1948, with Israel<U+2019>s existence in the balance during the War of Independence, our spies went undercover in Beirut, where they spent the next two years operating out of a kiosk, collecting intelligence, and sending messages back to Israel via a radio whose antenna was disguised as a clothesline. While performing their dangerous work these men were often unsure to whom they were reporting, and sometimes even who they<U+2019>d become. Of the dozen spies in the Arab Section at the war<U+2019>s outbreak, five were caught and executed. But in the end the Arab Section would emerge, improbably, as the nucleus of the Mossad, Israel<U+2019>s vaunted intelligence agency. Spies of No Country is about the slippery identities of these young spies, but it<U+2019>s also about Israel<U+2019>s own complicated and fascinating identity. Israel sees itself and presents itself as a Western nation, when in fact more than half the country has Middle Eastern roots and traditions, like the spies of this story. And, according to Friedman, that goes a long way toward explaining the life and politics of the country, and why it often baffles the West. For anyone interested in real-life spies and the paradoxes of the Middle East, Spies of No Country is an intimate story with global significance. "--